Pemberdayaan Masyarakat untuk Pencegahan Faktor Risiko Penyakit Tidak Menular (Studi Pada Pedesaan Di Yogyakarta) - Heni Trisnowati (Media Kesehatan Masyarakat Indonesia, 2018)
Non-Communicable Diseases (NCDs) are the leading cause of death in the world. NCDs dominated causeof death in Indonesia, mainly in Yogyakarta. This study aim to initiate a community intervention program throughcommunity empowerment to control risk factors for NCDs in Indonesia, especially in a rural area of Yogyakarta.This study used qualitative methods where data were collected by focus group discussions and in-depth interviews.There were 23 informants of community leaders and health workers. Tematik content analysis was used to analysedata. The process of community empowerment for the prevention and control of NCDs in Modinan are as follows:1) building public trust through meetings with community leaders to discuss about NCDs; 2) raising publicawareness through health cadre meetings and conducting FGD; 3) developing health promotion programs; 4)organising health promotion activities on “CERDIK Behavior” includes : routine medical chek up, not smokingdoing physical activity, a balanced diet, adequate rest and manage stress; 5) initiation to maintenance program.In Summary, Empowerment is one of health promotion strategies to prevent risk factors for NCDs. The involvementof community leaders, positive perception and knowledge about NCDs of health cadres determine the successof the program.